Improvement and effect analysis of guide signs considering the elderly - KANAZAWA, Hiroaki; NISHIDA, Tadashi; YAMAMOTO, Wataru; SATO, Hisanaga (Traffic Sciences, 2023)
In order to solve the problems faced by elderly drivers, such as the recent increase in wrong-way driving and accidents, previous research conducted a survey of subjects driving on highways and proposed improvements to guidance signs that take into consideration the driving characteristics of elderly drivers. This paper presents the implementation of improvement proposals that were subsequently implemented, and as a result of verifying the effectiveness of the countermeasures using ETC 2.0 probe data, it is clear that the frequency of sudden braking was reduced by 6% at a point 300m before the tollgate on the main line.